Evaluation of hand grip strength and range of movement of the upper limb in children with Polyarticular Hypermobility (PH) - Aneta Przymuszała; Magdalena Gębska (Kazimierz Wielki University, 2018)
Introduction Modern rehabilitation puts a great emphasis on early detection of faulty posture in children and adolescents. Unfortunately, proper recognition of joint hypermobility is neglected. Implementation of diagnostics and appropriate rehabilitation procedures in early stages of the disease will allow to prevent the occurrence of musculoskeletal diseases among those patients. Aim The aim of the study was to assess grip strength and mobility of the upper limb in children with polyarticular hypermobility. Materials and Methods The study was conducted on a group of children (n = 35), from 6 to 11 years old, who had been diagnosed with joint hypermobility using Beighton score criteria. The control group consisted of 35 healthy children of the same age. In all children measurement of grip strength was conducted using manual dynamometer and range of motion of the upper extremity joints was measured using a goniometer. Conclusions Conducted research showed that increased range of motion of joints of the upper extremity does not influence hand grip strength. Range of motion in both groups showed statistically significant differences.